Functional imaging by controlled nonlinear optical phenomena - Isobe, Keisuke (John Wiley & Sons Inc, 2014)
"This book gives an overview of the nonlinear optical process by ultrafast laser pulses and explains how the basics of nonlinear optical microscopy led to the most advanced techniques of photo-controlled nonlinear optical microscopy"--Provided by publisher.; Includes bibliographical references and index.